ATIVIDADE MICROBIANA E ESTABILIDADE DE AGREGADOS EM SISTEMAS INTEGRADOS DE PRODUÇÃO AGROPECUÁRIA - BARBOSA, Ygor Iahnn; COÊLHO, Roseline da Silva; DUARTE, Isis Caroline da Silva1 (isis.carolini@hotmail.com; OLIVEIRA, Naelmo de Souza; SCHIAVO, Jolimar Antonio (ANAIS DO ENIC, 2023)
-